Textbook of pediatrics and child health - Del Mundo, Fe; Estrada, Felix A.; Santos-Ocampo, Perla D.; Navarro, Xerxes R. (Quezon City : JMC Press, 1990)
1. Introduction to pediatrics -- 2. Growth and development -- 3. Preventive pediatrics -- 4. Nutrition -- 5. Pediatric diagnosis -- 6. Antenatal disorders -- 7. The newborn -- 8. Immunology -- 9. Allergy -- 10. Infectious diseases -- 11. Respiratory system -- 12. Disorders of the digestive system -- 13. The kidneys and urinary tract -- 14. Genitalia -- 15. Cardiovascular system --16. Connective tissue diseases -- 17. The nervous system -- 18. Psychologic disorders -- 19. Disorders of muscles, bones, and joints -- 20. Disturbance of metabolism -- 21. Endocrine disorders -- 22. Diseases of the skin - 23. The blood -- 24. Neoplastic conditions -- 25. Pediatric ophthalmology -- 26. Accidents, burns , and poisoning in children -- 27. The adolescent -- 28. Pediatric fluid and electrolyte therapy -- 29. Pediatric therapeutics -- 30. Appendix.
Includes bibliographical references and index.
Keywords: PEDIATRICS